ILMU DALAM ISLAM: SINTESIS PENDEKATAN BAYANI, BURHANI DAN IRFANI SEBAGAI KERANGKA EPISTEMOLOGI INTEGRATIF - Herdatama, Daffa Maulana Adha; Susilo, Dafa' Alifta Akbar (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
From an Islamic perspective, knowledge is understood as a map to truth that guides worship and builds civilisation. The Qur'an positions knowledge as a framework that combines rationality and the divine dimension, so that the process of seeking knowledge is always linked to devotion to God. The history of Islamic scholarship demonstrates methodological openness and creative dialogue with various scientific traditions, without losing sight of monotheism as its primary foundation. Islamic epistemology recognises revelation, reason, and the senses as three sources of knowledge that test, correct, and strengthen each other. The bayani, burhani, and irfani approaches are organised as complementary methods, thus giving rise to a paradigm of knowledge that is comprehensive, rational, and spiritual at the same time. Classical scholars such as Al-Farabi, Ibn Sina, and Al-Ghazali integrated rational and religious knowledge into a unified framework of thought. Axiologically, knowledge in Islam is oriented toward the benefit of God, with the etiquette of seeking knowledge emphasising the obligations of fardhu 'ain (obligatory duty) and fardhu kifayah (obligatory duty). In the context of Islamic religious universities in Indonesia, the integration of knowledge and religion has become a strategic agenda, particularly amid the disruptions of the digital era. Digital literacy, technological ethics, and the use of knowledge to uphold human dignity are essential pillars for the development of civilised education and technology. This research emphasises that knowledge is directed at developing faithful, knowledgeable, and noble individuals capable of responding to global challenges critically, creatively, humanely, and responsibly.